2002
DOI: 10.1016/s0006-3223(02)01439-7
|View full text |Cite
|
Sign up to set email alerts
|

Glia pathology in the prefrontal cortex in alcohol dependence with and without depressive symptoms

Abstract: Alcohol dependence is characterized by decreases in both density and size of glia in the dlPFC. Glial pathology may be more severe in Alc subjects with depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 63 publications
9
94
1
2
Order By: Relevance
“…These data suggest that increased density only occurred in a subset of the NAcore astrocyte population, which is consistent with earlier reports showing that only a subset of ALDH1L1 þ cells co-express GFAP (Cahoy et al, 2008). Additionally, a similar finding of altered GFAP þ astrocyte density, yet unchanged GFAP expression, was previously observed in EtOH-dependent human brain (Miguel-Hidalgo et al, 2002). While the specific ramifications of increased GFAP þ astrocyte density concerning motivated behavior remain unknown, it has been shown that increased astrocyte density can mitigate the impact of neurotoxic peroxide production that occurs during cytochrome P450-mediated metabolism of EtOH (Desagher et al, 1996).…”
Section: Behavioral Relevance Of Astrocyte Densitysupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that increased density only occurred in a subset of the NAcore astrocyte population, which is consistent with earlier reports showing that only a subset of ALDH1L1 þ cells co-express GFAP (Cahoy et al, 2008). Additionally, a similar finding of altered GFAP þ astrocyte density, yet unchanged GFAP expression, was previously observed in EtOH-dependent human brain (Miguel-Hidalgo et al, 2002). While the specific ramifications of increased GFAP þ astrocyte density concerning motivated behavior remain unknown, it has been shown that increased astrocyte density can mitigate the impact of neurotoxic peroxide production that occurs during cytochrome P450-mediated metabolism of EtOH (Desagher et al, 1996).…”
Section: Behavioral Relevance Of Astrocyte Densitysupporting
confidence: 92%
“…Additionally, rat strains that had selfadministered more morphine expressed more GFAP in the ventral tegmental area (Beitner-Johnson et al, 1993). In the prefrontal cortex, prelimbic GFAP þ astrocyte density was lower in rats that exhibited higher ethanol (EtOH) preference (Miguel-Hidalgo, 2005) while dorsolateral astrocyte density was lower in EtOH-dependent humans (Miguel-Hidalgo et al, 2002). These studies illustrate that astrocytes respond to commonly abused substances in a region-specific manner.…”
Section: Introductionmentioning
confidence: 81%
“…Excess extracellular fluid is presumed to be quickly drained into the ventricular system to be absorbed by venous sinuses, but excretion of fluid into vasculature of the brain parenchyma has also been proposed (Bloch et al, 2006). Shrinkage of brain cells and their processes (Obernier et al, 2002) might occur in the absence of gross tissue volume loss (Miguel-Hidalgo et al, 2002). Alternatively, tissue volume loss in this study sample may have been too small or too widely distributed to detect in any single region.…”
Section: Discussionmentioning
confidence: 92%
“…This gene is abundantly expressed in glial cells of the central nervous system and can be used as a marker for glial cell density and health. It is decreased in the FC of human adult alcoholics and more so in alcoholics with depressive symptoms (Miguel-Hidalgo et al, 2002). Humans with a history of chronic alcoholism have been found to have substantial glial pathology in the FC irrespective of current alcohol use or liver pathology (Cullen & Halliday, 1994).…”
Section: Within-region Analysismentioning
confidence: 99%